Transient Receptor Potential Vanilloid 1 Expression Mediates Capsaicin-Induced Cell Death - Ramírez-Barrantes, Ricardo; Córdova, Claudio; Gatica, Sebastian; Rodriguez, Belén; Lozano, Carlo; Marchant, Ivanny; Echeverria, Cesar; Simon, Felipe; Olivero, Pablo (Frontiers in Physiology, 2018)
The transient receptor potential (TRP) ion channel family consists of a broad variety of non-selective cation channels that integrate environmental physicochemical signals for dynamic homeostatic control. Involved in a variety of cellular physiological processes, TRP channels are fundamental to the control of the cell life cycle. TRP channels from the vanilloid (TRPV) family have been directly implicated in cell death. TRPV1 is activated by pain-inducing stimuli, including inflammatory endovanilloids and pungent exovanilloids, such as capsaicin (CAP). TRPV1 activation by high doses of CAP (>10µM) leads to necrosis, but also exhibits apoptotic characteristics. However, CAP dose-response studies are lacking in order to determine whether CAP-induced cell death occurs preferentially via necrosis or apoptosis. In addition, it is not known whether cytosolic Ca2+ and mitochondrial dysfunction participates in CAP-induced TRPV1-mediated cell death. By using TRPV1-transfected HeLa cells, we investigated the underlying mechanisms involved in CAP-induced TRPV1-mediated cell death, the dependence of CAP dose and the participation of mitochondrial dysfunction and cytosolic Ca2+ increase. Together, our results contribute to elucidate the pathophysiological steps that follow after TRPV1 stimulation with CAP. Low concentrations of CAP (1µM) induce cell death by a mechanism involving a TRPV1-mediated rapid and transient intracellular Ca2+ increase that stimulates plasma membrane depolarization, thereby compromising plasma membrane integrity and ultimately leading to cell death. Meanwhile, higher doses of CAP induce cell death via a TRPV1-independent mechanism, involving a slow and persistent intracellular Ca2+ increase that induces mitochondrial dysfunction, plasma membrane depolarization, plasma membrane loss of integrity, and ultimately, cell death.